MoSx-coated NbS2 nanoflakes grown on glass carbon: an advanced electrocatalyst for the hydrogen evolution reaction. Issue 7 (2nd February 2018) - Zhou, Xiaofeng; Lin, Shi-Hsin; Yang, Xiulin; Li, Henan; Hedhili, Mohamed Nejib; Li, Lain-Jong; Zhang, Wenjing; Shi, Yumeng
Abstract : MoS x -coated NbS2 nanoflakes are promising electrocatalyst for hydrogen evolution reaction. Abstract : Recent experimental and theoretical studies have demonstrated that two-dimensional (2D) transition metal dichalcogenide (TMDC) nanoflakes are one of the most promising candidates for non-noblemetal electrocatalysts for hydrogen evolution reaction (HER). However, it is still challenging to optimize their conductivity and enrich active sites for highly efficient electrochemical performance. Herein, we report a chemical vapor deposition (CVD) and thermal annealing two-step strategy to controllably synthesize hybrid electrocatalysts consisting of metallic NbS2 nanoflake backbones and a highly catalytic active MoS x nanocrystalline shell on polished commercial glass carbon (GC). In addition, the amount of MoS x in the hybrids can be easily adjusted. We first demonstrate that a small amount of MoS x significantly promotes the HER activity of 2D NbS2 nanoflakes, which is in good agreement with the density functional theory (DFT) calculation results. Moreover, the optimized MoS x @NbS2 /GC electrocatalyst displays superior HER activity with overpotential of −164 mV at −10 mA cm −2, a small Tafel slope of 43.2 mV dec −1, and prominent electrochemical stability. This study provides a new path for enhancing the HER performance of 2D TMDC nanoflakes.